SEVERAL ELEMENTS OF SEED PRODUCTIVITY IN CUCUMBER CULTIVARS BRED AT VNIISSOK - I. B. Korotseva (Ovoŝi Rossii, 2017)
Routine breeding work for cucumber cultivar and hybrid maintenance and their multiplication is carried out at Laboratory of Cucumber and Gourd Breeding and Seed Production, VNIISSOK. The original seeds of 5-6 cultivars or lines of cucumber are annually produced in open field and winter greenhouses at Experimental Production Division, FGBNU VNIISSOK. The seed productivity of cucumber depended on the number of seed bearers on the plant, size of seed bearers and a number of seeds in a fruit, as well as seed plumpness and seed fineness and etc. The condition of growing, such as meteorological factors, nutrition rates, cultivation technology, diseases and pests, cultivar specification influence on seed productivity and the traits mentioned above. The results given summarized multi-year data on 1000 seed weight and number of seeds in a fruits of bee-pollinated cultivars and hybrids, such as ‘Izyaschiy’, ‘Muromskiy 36’, ‘Viyaznikovskiy 37’, ‘Vodoley’, ‘Electron 2’, ‘Yedinstvo’, ‘Korotishka’, ‘Krepish F1’, ‘Brunet F1’. In open field the 1000 seed weight significantly varied among cultivars from 16.6 g. in ‘Viyaznikovskiy 37’ to 24.1 g. in ‘Yedinstvo’. The cultivars ‘Muromskiy 36’, ‘Viyaznikovskiy 37’ and ‘Izyaschiy’ were of the earlies ripening ones and had frailest seeds. Mid ripening cultivars ‘Edinstvo’ was distinguished by the biggest and plumpest seeds that were produced in open field as well as in greenhouse. 1000 seed weight in most cucumber cultivars was higher in open field than in greenhouse by 3.5-10.7 g., whereas this difference was more significant among hybrids. The film mulching increased 1000 seed weight. In seed fruits of bee-pollinated cultivars ‘Vodoley’ and ‘Electron 2’ and ‘Yedinstvo’, there were 250-259 seeds. This characteristic was the most stable in ‘Yedinstvo’. A problem with seed production occurs in cultivars of bush type ‘Korotishka’ and ‘Maliyutka’ because of the small number of seeds in a fruit as compared with other cultivars.